Osteoprotegerin and breast cancer risk by hormone receptor subtype: a nested case-control study in the EPIC cohort. Issue 1 (December 2017) - Fortner, Renée; Sarink, Danja; Schock, Helena; Johnson, Theron; Tjønneland, Anne; Olsen, Anja; Overvad, Kim; Affret, Aurélie; His, Mathilde; Boutron-Ruault, Marie-Christine; Boeing, Heiner; Trichopoulou, Antonia; et al.
Abstract Background Circulating osteoprotegerin (OPG), a member of the receptor activator of nuclear factor kappa-B (RANK) axis, may influence breast cancer risk via its role as the decoy receptor for both the RANK ligand (RANKL) and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL). Circulating OPG and breast cancer risk has been examined in only one prior study. Methods A case-control study was nested in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. A total of 2008 incident invasive breast cancer cases (estrogen receptor (ER)+, n = 1622; ER–, n = 386), matched 1:1 to controls, were included in the analysis. Women were predominantly postmenopausal at blood collection (77%); postmenopausal women included users and non-users of postmenopausal hormone therapy (HT). Serum OPG was quantified with an electrochemiluminescence assay. Relative risks (RRs) and 95% confidence intervals (CIs) were calculated using conditional logistic regression. Results The associations between OPG and ER+ and ER– breast cancer differed significantly. Higher concentrations of OPG were associated with increased risk of ER– breast cancer (top vs. bottom tertile RR = 1.93 [95% CI 1.24–3.02];p trend = 0.03). We observed a suggestive inverse association for ER+ disease overall and among women premenopausal at blood collection. Results for ER– disease did not differ by menopausal status at blood collection (p het = 0.97), and we observed no heterogeneity by HT use at blood collection (p het ≥ 0.43) or age at breast cancer diagnosis (p het ≥ 0.30). Conclusions This study provides the first prospective data on OPG and breast cancer risk by hormone receptor subtype. High circulating OPG may represent a novel risk factor for ER– breast cancer.